Explorando narrativas multimodais digitais na educação linguística em inglês: uma análise autoetnográfica da prática docente - Santana, José Raimundo dos Santos (2024)
This autoethnographic work aimed at analyzing the potentialities and/or limitations of a teaching practice involving digital multimodal narratives in English language education. To carry out this study, I rely, among other sources, on the theoretical assumptions that guide literacy theory – more specifically digital literacies (Lankshear; Knobel, 2006a, 2006b, 2012; Nascimento; Knobel, 2017; Zacchi, 2018a; Nascimento; Santos, 2020); studies on decoloniality (Sousa Santos, 2018; Walsh, 2013; Matos, 2019; Rezende et al., 2020; Menezes De Souza; Hashiguti, 2022), multimodality (Kress, 2010; Dionísio, 2014; Zacchi, 2016; Façanha, 2018), language education (Mattos, 2018; Siqueira, 2018; Zacchi, 2018b; Ferraz, 2018), and ecological approach (Reyes; Iddings; Feller, 2016; Iddings, 2018). Thus, starting from the general objective of analyzing the mentioned potentialities and/or limitations, this work has the following specific objectives: a) explore the meanings constructed by the teacher (myself) in the face of opportunities provided by the proposal of English language education; b) establish connections between the life stories of the teacher/researcher, the adoption of digital technologies, and the development of digital literacies in English language teaching; c) discuss the meanings (de/re)constructed by myself (the teacher) in the adoption of a decolonial, multimodal, and English language education perspective in the process of developing a didactic sequence; d) reflect on how my previous pedagogical and personal experiences reflect on my choices and affect the construction of the didactic sequence; and e) identify the contributions of using the ecological approach in the construction of the proposal. The methodological path includes the construction and analysis of the development of a didactic sequence idealized by the researcher for a public school in Capela/SE, using the Storyjumper platform. It is an autoethnographic investigation, whose data is generated through my experiences with the didactic sequence, which are registered on a multimodal field diary created by me within the aforementioned platform. The constant records, as well as the didactic sequence, are analyzed based on narrative coding (Saldaña, 2009). Through this study, I realized that using multimodal narratives made it possible to identify the ideological representations and colonialities inherent to my pedagogical practices as an English language teacher, as well as involved processes of significant dis/re/constructions and dis/learning during the elaboration of the didactic sequence. Exploring digital literacies, multimodality and decoloniality proved to be challenging given my limitations when trying to connect theory and practice; the imbrications and overlaps of multiple identities highlighted an internal obstacle in pedagogical practice; and the ecological approach allowed me to recognize my interconnection with the surrounding environment, as part of a network of (formal and informal) knowledge. Finally, I hope that this study contributes to the advancement of discussions on English language teaching, from a perspective of language education, on the ecological approach and on multimodality. I also hope it helps expanding the scope of autoethnography as a research methodology in Applied Linguistics.